Climate-Driven High Primary Production and Contrasting Export Production in the Eastern North Pacific Subtropical Gyre - Yoon, Joo-Eun; Kim, Ju-Hyoung; Kim, Il-Nam (Frontiers in Marine Science, 2022)
The eastern North Pacific subtropical gyre (NPSG) contributes significantly to global primary production (PP) and export production (EP). In this study, we have investigated the impact of the North Pacific gyre oscillation (NPGO) mode on the temporal changes in the relationship between PP and EP in the eastern NPSG, using long-term time series of oceanographic observations at Station ALOHA. The positive NPGO phases (N2+: 1998‒2004, N4+: 2007‒2013), exhibiting a deeper mixed layer depth (MLD), coincided with high PP. Moreover, the N2+ phase showed high EP, associated with an increase in the nano-sized phytoplankton group, and inorganic and organic nitrogen-to-phosphorus ratios. However, multiple physical and biogeochemical factors, such as thermocline depression, and increase in pico-sized phytoplankton groups, smallest-sized mesozooplankton, and heterotrophic bacteria, have induced low EP during the N4+ phase, despite deep MLD and increased PP conditions. Enhanced stratification under prolonged warming indicates that the surface eastern NPSG may experience a permanent shift toward small cells.